Twenty-five years of research on oral and written corrective feedback in System - Li, Shaofeng; Vuono, Alyssa (System (Linköping), 2019)
This article provides a comprehensive and critical review of the research on various aspects of oral and written corrective feedback (CF) based on selected articles published in System over the past 25 years. The review starts with a comparison between oral and written CF, demonstrating that despite the discrepancies in the characteristics and pedagogical practices of the two types of CF, they have been examined from similar perspectives in the research. The striking similarity in the research themes makes it possible to follow the same template in organizing the research synthesis for each CF type. The synthesis for each CF type comprises three sections. Section 1 provides a taxonomy of the CF type in question and summarizes the findings of descriptive or observational research regarding how teachers provide CF and how students react to CF. Section 2 synthesizes the findings of experimental CF research regarding whether CF is effective in facilitating learning gains and what factors constrain its effectiveness. Section 3 discusses the research on teachers’ and students’ beliefs about the utility of CF and how it should be implemented in the classroom.